PENGENDALIAN MUTU KERNEL DENGAN METODE DMAIC PADA INDUSTRI PENGOLAHAN KELAPA SAWIT DI RIAU - Fitri, Ainil; Zulhamidi, Zulhamidi (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2020)
In 2021, the quality of kernels in one of the palm oil processing industries in Riau was found to exceed the set standard limit. This is of course a problem that can affect the quality of the product. So kernel quality control will be carried out using the DMAIC method (Define, Measure, Analyze, Improve, Control). From the results of the X water content control chart above, it can be concluded that the data is said to be abnormal because some of it exceeds the UCL. While in the control map R there is data that exceeds the control limit or is uncontrolled. This is because the difference in sample values has such a large distance. From the results of the X temperature control chart above, it can be concluded that the data is said to be abnormal because the data exceeds the LCL or UCL. While in the R control map there is data that exceeds the control limit or is uncontrolled. This is because the difference in sample values has such a large distance. The cause of the high level of impurities in the core. The use of Pareto diagrams to determine the cause of non-compliance with quality standards in kernels is due to the highest/dominant impurity content. The causes of non-compliance with kernel quality standards are due to machine and human factors such as damage to claybath and hydrocyclone machines and lack of SOPs being followed.